DERAJAT HALLUX VALGUS DAN TINGKAT NYERI GURU SMK SURAKARTA - Anissa Eka Septiani; Nur Rachmat; Fitri Khoirun Nisa (Medical Journal of Nusantara, 2025)
Background: The foot plays a vital role in supporting body weight and enabling locomotion. Improper foot care and footwear can lead to musculoskeletal disorders such as pain. One common condition is hallux valgus, a lateral deviation of the big toe that causes progressive pain and impairs joint function. Teachers, particularly those in vocational high schools, are at higher risk due to prolonged standing and the use of formal footwear. Objective: This study aims to determine the relationship and strength of association between the hallux valgus angle and pain intensity among public vocational high school teachers in Surakarta. Methods: A quantitative, observational analytic study with a cross-sectional design was conducted. Participants were selected using purposive sampling. The hallux valgus angle was measured using amplification angulus, and pain intensity was assessed. Data were analyzed using Spearman’s correlation test. Results: A significant positive correlation was found between the hallux valgus angle and pain intensity. For the right foot, the p-value was 0.028 with a correlation coefficient of 0.401 (moderate). For the left foot, the p-value was 0.038 with a correlation coefficient of 0.380 (low). Conclusion: There is a significant positive relationship between the hallux valgus angle and pain intensity among teachers, with moderate correlation on the right foot and low correlation on the left foot